Job motivation of personnel in the Department of Education, Religion and Culture of Nursery at Khwao Subdistrict Municipality, Selaphum District, Roi Et Province - Leanwilairat, Wichan; Kumhom, Naitawan (Journal of Thammawat, 2022)
The purpose of this study was to study the level of Job motivation of personnel in the Department of Education, Religion and Culture of Nursery at Khwao Subdistrict Municipality, Selaphum District, Roi Et Province And to compare levels Job motivation of personnel in the Department of Education, Religion and Culture ofNursery at Khwao Subdistrict Municipality, Selaphum District, Roi Et Province The sample consisted of 163 people consisting of the director Nursery / deputy director of 5 Nursery, educational institutions, Nursery 1, 9 persons, 26 Nursery 2, Nursery 3, 37 people, 60 Nursery 4, and 26 Nursery 5, obtained by specifying the sample size of Krajie and Morgan's table. And using a simple sampling method Tools used to collect data. Is a questionnaire with estimation level The consistency index between 0.60 - 1.00 and the reliability of the whole version is equal to .746. The statistic used in the analysis consists of percentage, mean, standard deviation. The test tee, the F value The results showed that Job motivation of personnel in the Department of Education, Religion and Culture of Nursery at Khwao Subdistrict Municipality, Selaphum District, Roi Et Province Overall is at a high level. When classified in each aspect found that the work motivation the relationship with the executives was at a high level, followed by the policy and management. And the smallest Job security